Bounding Topology via Geometry, $A$-Simple Fundamental Groups (Communications in Mathematical Research, 2020)
We call a group $A$-simple, if it has no non-trivial normal abelian sub-group. We will present finiteness results in controlled topology via geometryon manifolds whose fundamental groups are $A$-simple.